2009
DOI: 10.1016/j.jbankfin.2009.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Consumption smoothing channels in open economies

Abstract: We recognize that intertemporal models of the current account (Frankel and Razin with Yuen 1996, or Baxter andCrucini 1993) imply a theory of consumption smoothing channels, and thus we build an empirical model on the theoretical foundations of Sachs (1982)'s optimizing model in order to analyze the intertemporal smoothing role of saving components (fixed investments, inventories and trade balance). The estimation is conducted in a VAR framework, in which the minimal identifying restrictions are consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…While several studies have explored perfect risk‐sharing tests at the aggregate level (e.g., Canova and Ravn ; Lewis ), for estimating intertemporal smoothing, researchers have typically based their analysis on testing the life cycle/permanent income hypothesis employing aggregate country‐level data (e.g., Campbell and Mankiw ; Crucini ). With regards to empirical findings, studies have usually found intranational risk sharing to be around 70% and international risk sharing to be around 10%, while intertemporal smoothing is roughly almost 50% (Asdrubali and Kim , , ; Sørensen and Yosha ).…”
mentioning
confidence: 99%
“…While several studies have explored perfect risk‐sharing tests at the aggregate level (e.g., Canova and Ravn ; Lewis ), for estimating intertemporal smoothing, researchers have typically based their analysis on testing the life cycle/permanent income hypothesis employing aggregate country‐level data (e.g., Campbell and Mankiw ; Crucini ). With regards to empirical findings, studies have usually found intranational risk sharing to be around 70% and international risk sharing to be around 10%, while intertemporal smoothing is roughly almost 50% (Asdrubali and Kim , , ; Sørensen and Yosha ).…”
mentioning
confidence: 99%